2020
DOI: 10.22159/ijap.2020.v12s1.ff050
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Stability of Resveratrol-Conjugated Gold Nanoparticles Modified With Polyethylene Glycol

Abstract: Objective: Gold nanoparticles (AuNPs) are highly useful for drug delivery, but their application is limited by their stability as they readily aggregate.This issue can be prevented by adding a stabilizing agent such as resveratrol (RSV), which is a polyphenol derived from plants, that is used to preventcancer. Therefore, we propose a novel method to prepare stable RSV-conjugated nanoparticles modified with polyethylene glycol (RSV-AuNP-PEG).Methods: In the first step, the Turkevich method was used to synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Prior observations by Park et al (21) indicated the appearance of absorbance at 547 nm and successful synthesis of Res-AuNPs. Similarly, Iswandana et al (17) observed ultraviolet-visible spectra of gold nanoparticles with a peak at 528.50 nm and AuNPs-PEG-Res absorbed light at 529 nm. The chemical surfaces and functional group endpoints of AuNPs and AuNPs-PEG-Res were characterized using FT-IR spectroscopy.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Prior observations by Park et al (21) indicated the appearance of absorbance at 547 nm and successful synthesis of Res-AuNPs. Similarly, Iswandana et al (17) observed ultraviolet-visible spectra of gold nanoparticles with a peak at 528.50 nm and AuNPs-PEG-Res absorbed light at 529 nm. The chemical surfaces and functional group endpoints of AuNPs and AuNPs-PEG-Res were characterized using FT-IR spectroscopy.…”
Section: Discussionmentioning
confidence: 76%
“…The only difference observed in the FTIR of AuNPs-PEG-Res over Res is the shift of a broad band observed between 3259.70 cm −1 , 2113.99 cm −1 and 1635.64 cm −1 . The appearance of a peak observed at 3749.64 cm −1 is related to the PEG-(N-H) (17) . The strong diffraction peaks with 2θ values at 38.2º, 44.4º, 64.7º, and 77.7º are associated with the Bragg's reflections of 111, 200, 220, and 311 planes related to the face-centered cubic (FCC) of AuNPs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation